1999
DOI: 10.1177/014556139907800712
|View full text |Cite
|
Sign up to set email alerts
|

Tracheostomy for Ventilator Dependence in the Elderly Patient: A Preliminary Report

Abstract: A bst ract With advances in medi cal techn ology and increasing numbers of elderly patient s surviving acut e intensive care unit admissions, otolaryngolog ic consultat ion rega rdin g trach eostomy fo r ventilato r-dependen t patients is expected to continue increasin g. Ho wever, established treatm ent guide lines and defin ed out com es in term s of health status, qua lity of life, and medi ca l costs are lacking in this emotionally delicate setting. A retrospective case review of the outcomes of 19 elderly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…Few studies have evaluated outcomes in elderly, severely ill patients requiring tracheotomies. At least one other study reported data similar to those presented here,7; namely, that a tracheotomy may not always constitute the best airway management in the elderly and severely ill patient with respiratory failure.…”
Section: Discussionsupporting
confidence: 76%
“…Few studies have evaluated outcomes in elderly, severely ill patients requiring tracheotomies. At least one other study reported data similar to those presented here,7; namely, that a tracheotomy may not always constitute the best airway management in the elderly and severely ill patient with respiratory failure.…”
Section: Discussionsupporting
confidence: 76%
“…The long-term outcomes in this patient population are known to be poor, and even the short-term mortality rates are significant. 1,2 The relatively high likelihood of poor short-term outcomes in these patients compels the clinician to look for ways to identify those with a better chance for short-term survival. Clearly, tracheotomy is not always indicated in patients who have a high probability of short-term mortality, but to the knowledge of the authors, there have not been any studies to assess the reliability of prognostic indicators in this patient population.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Patients with persistent airway obstruction have continued benefit from prolonged tracheotomy, and removal is contraindicated.…”
mentioning
confidence: 99%